Riparian plant community change and alien plant invasions following geomorphological change in the Sabie River, Kruger National Park, South Africa - Sibiya, Thabang Euginia (Stellenbosch : Stellenbosch University, 2019)
Thesis (MScConsEcol)--Stellenbosch University, 2019.